WAYS TO INCREASE THE EFFECTIVENESS OF ACADEMIC RESEARCH IN LEGAL REFORMS AND IMPLEMENT THEM INTO PRACTICE (Universal International Scientific Journal, 2026)
This article analyzes the role of academic research in legal reforms, the issues ofincreasing their effectiveness, and ways to implement scientific results into legal practice
Keywords: legal reforms; academic research; scientific results